Pregnancy-Related Complications in Patients With Fibromuscular Dysplasia: A Report From the European/International Fibromuscular Dysplasia Registry. Issue 2 (August 2020) - Pappaccogli, Marco; Prejbisz, Aleksander; Ciurică, Simina; Bruno, Rosa Maria; Aniszczuk-Hybiak, Anna; Bracalente, Irene; De Backer, Tine; Debiève, Frédéric; Delmotte, Philippe; Di Monaco, Silvia; Jarraya, Faiçal; Gordin, Daniel; et al.
Abstract : Current literature suggests a higher risk of pregnancy-related complications in patients with renal fibromuscular dysplasia (FMD). The aim of our study was to assess the nature and prevalence of pregnancy-related complications in patients subsequently diagnosed with FMD. A call for participation was sent to centers contributing to the European/International FMD Registry. Patients with at least 1 pregnancy were included. Data on pregnancy were collected through medical files and FMD characteristics through the European/International FMD Registry. Data from 534 pregnancies were obtained in 237 patients. Despite the fact that, in 96% of cases, FMD was not diagnosed before pregnancy, 40% of women (n=93) experienced pregnancy-related complications, mostly gestational hypertension (25%) and preterm birth (20%), while preeclampsia was reported in only 7.5%. Only 1 patient experienced arterial dissection and another patient an aneurysm rupture. When compared with patients without pregnancy-related complications, patients with complicated pregnancies were younger at FMD diagnosis (43 versus 51 years old; P <0.001) and had a lower prevalence of cerebrovascular FMD (30% versus 52%; P =0.003) but underwent more often renal revascularization (63% versus 40%, P <0.001). In conclusion, the prevalence of pregnancy-related complications such as gestational hypertension and preterm birth was high in patients with FMD, probably related to the severity of renal FMD. However, the prevalence of preeclampsia and arterial complications was low/moderate. These findings emphasize the need to screen hypertensive women for FMD to ensure revascularization before pregnancy if indicated and appropriate follow-up during pregnancy, without discouraging patients with FMD from considering pregnancy. Abstract : Supplemental Digital Content is available in the text.